Location of single line-to-ground faults on distribution feeders using voltage measurements - Pereira, R. A F [UNESP]; Da Silva, L. G W [UNESP]; Kezunovic, M.; Mantovani, J. R S [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2006)
This paper proposes a dedicated algorithm for lation of single line-to-ground faults in distribution systems. The proposed algorithm uses voltage and current phasors measured at the substation level, voltage magnitudes measured at some buses of the feeder, a database containing electrical, operational and topological parameters of the distribution networks, and fault simulation. Voltage measurements can be obtained using power quality devices already installed on the feeders or using voltage measurement devices dedicated for fault location. Using the proposed algorithm, likely faulted points that are located on feeder laterals geographically far from the actual faulted point are excluded from the results. Assessment of the algorithm efficiency was carried out using a 238 buses real-life distribution feeder. The results show that the proposed algorithm is robust for performing fast and efficient fault location for sustained single line-to-ground faults requiring less than 5% of the feeder buses to be covered by voltage measurement devices. © 2006 IEEE.
Keywords: Fault Location; Power Distribution; Voltage Measurement; Algorithm efficiency; Current phasors; Distribution feeders; Distribution systems; Fault simulation; Feeder bus; Power distributions; Power quality devices; Single line-to-ground faults; SOME-Bus; Topological parameters; Voltage magnitude; Algorithms; Computer simulation; Current limiting reactors; Electric fault location; Electric grounding; Feeding; Underground cables; Voltage measurement; Power quality